A Pseudorabies Virus Recombinant Simultaneously Lacking the Major Tegument Proteins Encoded by the UL46, UL47, UL48, and UL49 Genes Is Viable in Cultured Cells - Fuchs, Walter (American Society for Microbiology, 2003)
The UL46, UL47, UL48, and UL49 genes, which encode major tegument proteins, are conserved in most alphaherpesvirus genomes. However, the relative importance of each of these proteins for replication of individual alphaherpesviruses appears to be different. Recently, we demonstrated that single deletions of UL47 or UL48 impair maturation and egress of pseudorabies virus (PrV) particles to different extents, whereas deletions of UL46 or UL49 have no significant effects on virus replication in cell culture (W. Fuchs, H. Granzow, B. G. Klupp, M. Kopp, and T. C. Mettenleiter, J. Virol. 76:6729-6742, 2002; M. Kopp, B. G. Klupp, H. Granzow, W. Fuchs, and T. C. Mettenleiter, J. Virol. 76:8820-8833, 2002). To test for possible functional redundancy between the four tegument proteins, a quadruple gene deletion mutant (PrV-ΔUL46-49) was generated and characterized in vitro. Although plaque formation by this mutant was almost abolished and maximum titers were reduced more than 100-fold compared to those of parental wild-type virus, PrV-ΔUL46-49 could be propagated and serially passaged in noncomplementing porcine and rabbit kidney cells. Electron-microscopic studies revealed that nucleocapsid formation and egress of PrV-ΔUL46-49 from the host cell nucleus were not affected, but secondary envelopment of nucleocapsids in the cytoplasm was only rarely observed. The replication defect of PrV-ΔUL46-49 could be fully corrected by reinsertion of the UL46-to-UL49 gene cluster. Plaque sizes and virus titers were only slightly increased after restoration of only UL47 expression, whereas repair of only UL48 resulted in a significant increase in replication capacity to the level of a UL47 deletion mutant. In conclusion, we show that none of the UL46 to UL49 tegument proteins is absolutely required for productive replication of PrV. Moreover, our data indicate that the UL47 and UL48 proteins function independently during cell-to-cell spread and virus egress.